THE LOW ROTATION 1 PHASE AC GENERATOR USING MULTIPLE STATOR AND ROTOR METHOD IN THE FLOATING-HYDRO POWER PLANT - Ahmad Afif Amrulloh; Basuki Winarno; Yuli Prasetyo; Raden Jasa Kusumo Haryo (Merdeka Malang University, 2019)
Abstract— Electrical energy is the most vital necessity in daily human’s life. The need of electrical energy has been continuously increasing along with the industry and society development. Indonesia is a tropical country with loads of energy sources which one of them is the new renewable energy sources. There are still many unexploited river flows that possess potentials as energy sources. The Floating-Hydro power plant is one of portable power plants harnessing the river flows as the energy source. In this study, the Low Rotation 1 Phase AC Generator Using Multiple Stator and Rotor Method in the Floating-Hydro Power Plant was designed. This generator consisted of several stators and rotors. The stator was strung together using the enamel wire. As in accordance to the design outcome, the number of stator windings was 364 per coil, the space between windings was 4cm, and the stator diameter was 25cm. Meanwhile, the rotor consisted of Neodymium (NdFeB) type permanent magnet which was going to be induced into the stator. Every rotor consisted of 10 pieces of permanent magnet with a space between magnets was 2cm. The experiment result, which was performed on the 1 phase axial generator using 2 stators and 3 rotors with loads in the form of 3 pieces of 35W 12VAC lamps, generated voltages of 2,1 VAC with currents of 0,03A at the low speed of 100rpm. Meanwhile, at the speed of 1200rpm, it generated voltages of 10,68VAC with currents of 0,23A. DOI : https://doi.org/10.26905/jeemecs.v2i2.3205